1992
DOI: 10.1007/bf01923508
|View full text |Cite
|
Sign up to set email alerts
|

Proteases and proteolysis in the lysosome

Abstract: Proteins sequestered by a non-selective bulk process within the lysosomes turn over with an apparent half-life of about 8 minutes and this rapid lysosomal proteolysis is initiated by endopeptidases, in particular by the cathepsins D and L. We describe also the cathepsins B and H which show mainly exopeptidase and only low endopeptidase activity. Especially cathepsin H is most probably the only lysosomal aminopeptidase in many cell types. Additionally, the properties of other mammalian lysosomal endo- and exope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
138
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(147 citation statements)
references
References 44 publications
7
138
0
2
Order By: Relevance
“…Lysosomes contain many cathepsins that are responsible for the degradation of proteins targeted to these vesicles (24). We previously demonstrated that the protease activity responsible for generating p40 was a cysteine protease (15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysosomes contain many cathepsins that are responsible for the degradation of proteins targeted to these vesicles (24). We previously demonstrated that the protease activity responsible for generating p40 was a cysteine protease (15).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this identity is the MCE's high level expression in spleen, liver, and kidney (15,24,42), stable activity at physiological pH (43), and its inability to bind concanavalin A (17). In addition, purified cathepsin B could generate p40 from MARCKS in a cell-free system.…”
Section: Fig 3 Chromatographic Elution Profiles and Immunoblot Analmentioning
confidence: 86%
“…45 Autophagy Autophagy, is a lysosomal degradation pathway for cytoplasmic components (for a review, see Klionsky and Emr, 10 Eskelinen 17 and Theos et al 46 ). Unlike the ubiquitin-proteasome degradation system responsible for degradation of short-lived proteins, autophagy is involved in the turnover of long-lived proteins, cellular macromolecules and whole organelles, 13,[47][48][49][50] acting as an essential physiological system for cellular homeostasis. 51 It has also been demonstrated that autophagy has an important role in neurodegenerative diseases, aging, cancer, type-II programmed cell death, antigen presentation, early neonatal stages and bacterial invasion (for a review, see Tanida et al 11 ).…”
Section: Biogenesis Of Mvbsmentioning
confidence: 99%
“…They are potent ubiquitously expressed endopeptidases with broad substrate specificity that work best at acidic pH and reducing redox conditions 8,9 . Cathepsin L-deficient (Ctsl À / À ) mice reproduce normally, although pups showed a slightly increased mortality during the weaning period 10 .…”
mentioning
confidence: 99%